Polymorphism of 11 Y Chromosome Short Tandem Repeat Markers among Malaysian Aborigines - Mohd Yussup, Sofia Sakina (Evol Bioinform Online, 2017)
The conventional technique such as patrilocality suggests some substantial effects on population diversity. With that, this particular study investigated the paternal line, specifically Scientific Working Group on DNA Analysis Methods (SWGDAM)-recommended Y-STR markers, namely, DYS19, DYS385, DYS389I/II, DYS390, DYS391, DYS392, DYS393, DYS438, and DYS439. These markers were tested to compare 184 Orang Asli individuals from 3 tribes found in Peninsular Malaysia. As a result, the haplotype diversity and the discrimination capacity obtained were 0.9987 and 0.9076, respectively. Besides, the most diverse marker was DYS385b, whereas the least was DYS391. Furthermore, the Senoi and Proto-Malay tribes were found to be the most distant, whereas the Senoi and Negrito clans were almost similar to each other. In addition, the analysis of molecular variance analysis revealed 82% of variance within the population, but only 18% of difference between the tribes. Finally, the phylogenetic trees constructed using Neighbour Joining and UPGMA (Unweighted Pair Group Method with Arithmetic Mean) displayed several clusters that were tribe specific. With that, future studies are projected to analyse individuals based on more specific sub-tribes.